Changing Economy – developing key skills for a new attitude - MIHALCIOIU, Raluca (Journal of Economic Development, Environment and People, 2016)
Go with the times or be gone in no time Our economy and society is marked by very rapid changes. We live in times of permanent changes in a breathtaking pace. This is accompanied by uncertainty, anxiety and general lethargy. We can recognize Phenomena such as these not only at individuals - undisputed right at each of us in varying degrees – but it also relates to all sectors, such as the economy, politics, society in its various areas.